Preparation of oligodeoxyribonucleoside methylphosphonates on a polystyrene support. - Miller, P S (1983)
An efficient procedure is described for synthesizing deoxyribonucleoside methylphosphonates on polystyrene polymer supports which involves condensing 5'-dimethoxytrityldeoxynucleoside 3'-methylphosphonates. The oligomers are removed from the support and the base protecting groups hydrolyzed by treatment with ethylenediamine in ethanol, which avoids hydrolysis of the methylphosphonate linkages. Two types of oligomers were synthesized: those containing only methylphosphonate linkages, d-Np(Np)nN, and those which terminate with a 5' nucleotide residue, dNp (Np)nN. The latter oligomers can be phosphorylated by polynucleotide kinase, and are separated by polyacrylamide gel electrophoresis according to their chain length. Piperdine randomly cleaves the oligomer methylphosphonate linkages and generates a series of shorter oligomers whose number corresponds to the length of the original oligomer. Apurinic sites introduced by acid treatment spontaneously hydrolyze to give oligomers which terminate with free 3' and 5' OH groups. These reactions may be used to characterize the oligomers.